2014
DOI: 10.1159/000367681
|View full text |Cite
|
Sign up to set email alerts
|

Very Old Patients on Hemodialysis: How They Start and Can We Predict Survival?

Abstract: Background: We describe circumstances of dialysis initiation, dialysis prescription and factors affecting survival in elderly patients. Methods: We included all incident patients ≥80 years old from a National Registry for which clinical and laboratory data at dialysis initiation could retrospectively be obtained. Results: Of 170 patients included, 24% had diabetes, 30% ischemic heart disease, 13% peripheral arterial disease, 15% active malignancy and 60% prior nephrology care. Mean creatinine was 672 ± 225 µmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 24 publications
2
8
1
Order By: Relevance
“…In our opinion, the early and intensive nephrology pre-dialysis care is the key to a successful dialysis treatment in octogenarians and nonagenarians. A very recent study from Slovenian national registry (170 patients ≥80 years) confirms these results [7]. Gubensek et al found in a multivariate analysis that only age and pre-dialysis nephrology care were independent predictors of survival.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…In our opinion, the early and intensive nephrology pre-dialysis care is the key to a successful dialysis treatment in octogenarians and nonagenarians. A very recent study from Slovenian national registry (170 patients ≥80 years) confirms these results [7]. Gubensek et al found in a multivariate analysis that only age and pre-dialysis nephrology care were independent predictors of survival.…”
Section: Discussionmentioning
confidence: 65%
“…Late referral is a well-known significant independent risk factor influencing dialysis patient's outcomes [7,11,12,13,14]. In a reverse approach, Jungers et al showed that longer duration of regular nephrological care in the pre-dialysis period is associated with better long-term survival on dialysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the first months after starting dialysis, mortality is higher in very elderly patients [7][8][9] . From the sixth month onward, the monthly hazard of death persists [7] , but the patients may also remain stable for many years to come [4,[10][11][12][13][14] . Finally, in all octogenarians and nonagenarians, we always face the process of dying including frailty, loss of autonomy, and heavy burden.…”
Section: Introductionmentioning
confidence: 99%